2009
DOI: 10.1183/09031936.00100708
|View full text |Cite
|
Sign up to set email alerts
|

Increased T-regulatory cells within lymphocyte follicles in moderate COPD

Abstract: Lymphoid follicles in the lung parenchyma are a characteristic feature of chronic obstructive pulmonary disease (COPD). There are reports of altered CD4 T-regulatory cell numbers in COPD lungs, but the location of these cells within COPD lung tissue specific follicles has not been investigated.The presence of CD4 + FOXP3 + T-regulatory cells was assessed in surgically resected lung tissue from 12 COPD patients, 11 smokers with normal lung function and seven nonsmokers by combined immunofluorescence and immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
53
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 27 publications
4
53
1
7
Order By: Relevance
“…By contrast, although previous data of PLUMB et al [5] indicated an increase in CD4 + T-cells in parenchymal LFs of moderate COPD patients, the present results do not show any significant difference in the follicular densities of B-cells, T-cells, macrophages or mature dendritic cells among clinical groups.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…By contrast, although previous data of PLUMB et al [5] indicated an increase in CD4 + T-cells in parenchymal LFs of moderate COPD patients, the present results do not show any significant difference in the follicular densities of B-cells, T-cells, macrophages or mature dendritic cells among clinical groups.…”
Section: Discussioncontrasting
confidence: 56%
“…We have stated that LFs were located in both the adventitia of airways and the parenchyma of pulmonary samples, as previously described [2][3][4][5][6]14]. However, the presence of LFs was also observed in the connective tissue of lobular septa and in the arteriolar adventitia, the later compartment being the most frequently occupied by LFs in COPD patients.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations